Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/nature20775
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for gating the high-conductance Ca2+-activated K+ channel

Abstract: The precise control of an ion channel’s gate by environmental stimuli is crucial to the fulfillment of its biological role. The gate in Slo1 channels is regulated by two separate stimuli, intracellular Ca2+ concentration and membrane voltage. Thus, Slo1 is central to understanding the relationship between intracellular Ca2+ and membrane excitability. Here we present the Slo1 structure in the absence of Ca2+ and compare it with the Ca2+-bound channel. Ca2+ binding at two unique binding sites per subunit stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
324
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(355 citation statements)
references
References 51 publications
21
324
2
Order By: Relevance
“…Expansion of RCK1 N-lobes induced by Na + is similar to the expansion documented in the Slo1 Ca 2+ - and voltage-activated K + channel induced by Ca 2+ (Wu et al, 2010; Yuan et al, 2012; Tao et al, 2016; Hite et al, 2016). The concomitant changes in the S1–S4 voltage-sensing domains observed in Slo1, however, are not observed in Slo2.2.…”
Section: Resultssupporting
confidence: 72%
“…Expansion of RCK1 N-lobes induced by Na + is similar to the expansion documented in the Slo1 Ca 2+ - and voltage-activated K + channel induced by Ca 2+ (Wu et al, 2010; Yuan et al, 2012; Tao et al, 2016; Hite et al, 2016). The concomitant changes in the S1–S4 voltage-sensing domains observed in Slo1, however, are not observed in Slo2.2.…”
Section: Resultssupporting
confidence: 72%
“…This segment is postulated to play a role in biogenesis, protein folding, and gating of these channels (37)(38)(39)(40)(41)(42)(43)(44)(45). Our NMR spectroscopy and Gd 3ϩ suppression data did not support the presence of a pre-S1 helix in Kv11.1 channels.…”
Section: Role Of S1 In Channel Inactivationcontrasting
confidence: 44%
“…The NMR data suggest that the transmembrane extent of S1 in Kv11.1 extends at least from Trp-410 to Leu-432, with a possible break or kink at Thr-425/Pro-426. The NMR data do not support a pre-S1 helical segment in Kv11.1 channels, a feature that is present in the structure of other voltage-gated ion channels (37)(38)(39)(40)(41)(42)(43) but not in the cryo-electron microscopy (cryo-EM) structure of rEAG (50).…”
Section: Structural Extent Of the S1 Helix Of Kv111 Channelsmentioning
confidence: 92%
See 1 more Smart Citation
“…A coupling of electrical signaling to Ca 2+ -mediated events allows this channel to regulate muscle contraction, hormone secretion and neuronal excitability 5051 . Recent Mg 2+ /Ca 2+ -free and Mg 2+ /Ca 2+ -bound cryo-EM structures of the full-length Slo1 channel from Aplysia californica demonstrated that the BK Ca channel is a tetramer with the transmembrane domain (TMD) on top, the first regulator of K + conductance (RCK1) domain in the middle and the RCK2 domain at the bottom (Figure 2) 5253 . The TMD includes S0 helix, a voltage-sensor domain (VSD) with S1–S4 helices and a pore domain (PD) with S5–S6 helices.…”
Section: Slo1 Bkca Channelmentioning
confidence: 99%